Genome-wide association studies identified novel SNPs associated with efficient biological nitrogen fixation in chickpea (Cicer arietinum L.) - S, Chandana B.; Mahto, Rohit Kumar; Singh, Rajesh Kumar; V, Ramachandra; Singh, K. K.; Kushwah, Sunita; Lavanya, Gera Roopa; Kudapa, Himabindu; Kumar Valluri, Vinod; Vemula, Anil Kumar; Yadav, Raju Ratan; Yadav, Lal Bahadur; et al. (Frontiers in Plant Science, 2025)
Chickpea (Cicer arietinum L.) is the second most important food legume crop, capable of converting atmospheric nitrogen (N2) into ammonia (NH3) in symbiotic association with Mesorhizobium cicero through a process called biological nitrogen fixation (BNF). BNF shows promise in effectively diminishing reliance on exogenous nitrogen applications, enhancing soil sustainability and productivity in pulse crops. Notably, there are limited studies on the molecular basis of root nodulation in chickpea. In order to identify new sources of highly nodulating genotypes and gain deep insights into genomic regions governing BNF, a diverse chickpea global germplasm collection (284) was evaluated for nodulation and yield traits in four different environments in an augmented randomized block design. The genotypes exhibited significant trait variation, encompassing all traits under study. Correlation analysis revealed a significant positive correlation of nodulation traits on yield within the chickpea population. The genotypes ICC 7390, ICC 15, ICC 8348, and ICC 2474 were identified as high nodulating across the locations. Genome-wide association studies (GWAS) identified noteworthy and stable marker–trait associations (MTAs) linked to the traits of interest. For the traits number of nodules (NON) and nodule fresh weight (NFW), 65 and 109 significant MTAs were identified, respectively. In addition, two SNPs, Ca1pos289.52482.1 and 6_33340878, identified in our earlier studies were validated by independent population studies, which are crucial in evaluating the accuracy and reliability of the projections. Subsequent analysis revealed that a substantial proportion of these MTAs were situated within intergenic regions, with the potential to modulate genes associated with the focal traits. The candidate genes identified could be converted to Kompetitive allele-specific PCR (KASP) markers and exploited in marker-assisted breeding, accentuating their impact on future chickpea breeding efforts.